2017
DOI: 10.3341/jkos.2017.58.8.952
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography-angiography: Comparison of the Foveal Avascular Zone between Diabetic Retinopathy and Normal Subjects

Abstract: Purpose:To evaluate the effectiveness of optical coherence tomography angiography (OCTA) in investigating changes in the area of the foveal avascular zone (FAZ) in patients with diabetic retinopathy (DR) and normal subjects. Methods: Eighty-five eyes of 50 DR patients and 50 eyes of 25 normal subjects were included. OCTA images of the FAZ were acquired using the split-spectrum amplitude decorrelation angiography algorithm of Optovue Avanti RTVue XR OCT. Patients were divided into three groups according to DR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The enlargement of the FAZ is positively correlated with the severity of DR. 16 Studies have shown that individuals with mild to moderate nonproliferative DR have a smaller FAZ growth rate, whereas individuals with proliferative DR have a larger FAZ growth rate. 17 , 18 Thus, the FAZ growth rate might be a hallmark feature of DR occurrence and progression.…”
mentioning
confidence: 99%
“…The enlargement of the FAZ is positively correlated with the severity of DR. 16 Studies have shown that individuals with mild to moderate nonproliferative DR have a smaller FAZ growth rate, whereas individuals with proliferative DR have a larger FAZ growth rate. 17 , 18 Thus, the FAZ growth rate might be a hallmark feature of DR occurrence and progression.…”
mentioning
confidence: 99%